Finding and treating both tuberculosis disease and latent infection during population-wide active case finding for tuberculosis elimination - Coleman, Mikaela; Nguyen, Thu-Anh; Luu, Boi Khanh; Hill, Jeremy; Ragonnet, Romain; Trauer, James M.; Fox, Greg J.; Marks, Guy B.; Marais, Ben J. (Frontiers in Medicine, 2023)
In recognition of the high rates of undetected tuberculosis in the community, the World Health Organization (WHO) encourages targeted active case finding (ACF) among “high-risk” populations. While this strategy has led to increased case detection in these populations, the epidemic impact of these interventions has not been demonstrated. Historical data suggest that population-wide (untargeted) ACF can interrupt transmission in high-incidence settings, but implementation remains lacking, despite recent advances in screening tools. The reservoir of latent infection—affecting up to a quarter of the global population –complicates elimination efforts by acting as a pool from which future tuberculosis cases may emerge, even after all active cases have been treated. A holistic case finding strategy that addresses both active disease and latent infection is likely to be the optimal approach for rapidly achieving sustainable progress toward TB elimination in a durable way, but safety and cost effectiveness have not been demonstrated. Sensitive, symptom-agnostic community screening, combined with effective tuberculosis treatment and prevention, should eliminate all infectious cases in the community, whilst identifying and treating people with latent infection will also eliminate tomorrow’s tuberculosis cases. If real strides toward global tuberculosis elimination are to be made, bold strategies are required using the best available tools and a long horizon for cost-benefit assessment.